2010
DOI: 10.1038/hr.2010.205
|View full text |Cite
|
Sign up to set email alerts
|

Different actions of losartan and ramipril on adipose tissue activity and vascular remodeling biomarkers in hypertensive patients

Abstract: We planned a randomized, double blind clinical trial to evaluate whether an antihypertensive intervention at the proximal or distal level of the renin-angiotensin-aldosterone system could have different effects on a broad range of innovative cardiovascular risk biomarkers. A total of 288 hypertensive Caucasian patients (115 men and 113 women), aged X18 years, were enrolled in this study. They were randomized to take losartan 50 mg per day or ramipril 5 mg per day for 1 month and titrated up to 100 mg per day a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…The results of some randomized controlled trials have reported increases in insulin sensitivity with ARB treatment compared with other antihypertensive treatments. [37][38][39][40][41][42][43][44] Conversely, our study and others demonstrated no change in whole-body insulin sensitivity measures during RAS. [45][46][47][48][49] The reason for this apparent discrepancy is unclear but differences in the particular ARB used, duration of treatment, methods used to assess insulin sensitivity, and/or study population may contribute.…”
Section: Discussionmentioning
confidence: 57%
“…The results of some randomized controlled trials have reported increases in insulin sensitivity with ARB treatment compared with other antihypertensive treatments. [37][38][39][40][41][42][43][44] Conversely, our study and others demonstrated no change in whole-body insulin sensitivity measures during RAS. [45][46][47][48][49] The reason for this apparent discrepancy is unclear but differences in the particular ARB used, duration of treatment, methods used to assess insulin sensitivity, and/or study population may contribute.…”
Section: Discussionmentioning
confidence: 57%
“…However, results obtained in further studies weren't so clear. Ferrari et al [9] showed the increase in plasma visfatin concentration after treatment with angiotensin II receptor AT 1 inhibitors, but not after using ACE-Is in 288 hypertensive patients. Contrary Eyileten et al [10] have showed the decrease of plasma visfatin concentration after treatment with ACE-Is in patients with diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…In few studies the effect of pharmacological blockade of RAA system on plasma visfatin level was described [8,9,10]. In the first study both the angiotensin converting enzyme inhibitors (ACE-Is) and angiotensin II receptor AT1 inhibitors use was followed by the increase of visfatin secretion from endothelial cells, adipocytes and myocytes [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within CCBs, candesartan, but not olmesartan therapy, over the period of a year resulted in increased adiponectin and insulin sensitivity in T2DM hypertensive patients, even though BP lowering was similar in both treatment groups [109]. When compared to the ACEI ramipril, losartan treatment significantly improved adiponectin levels and overall metabolic parameters while ramipril had no effect on adiponectin or any other metabolic markers [131]. In obese hypertensive patients, telmisartan, but not losartan raised serum adiponectin levels [132].…”
Section: Adiponectinmentioning
confidence: 99%